Automatic Closed-Loop Control Applied to TSN Scheduling - Torres Macías, Alitzel Galilea; Ramírez Treviño, Antonio; Briz Velasco, José Luis; Segarra Flor, Juan; Gracia Rodríguez, Álex; Blanco Alcaine, Héctor (Jornada de Jóvenes Investigadores del I3A, 2025)
A Time-Aware Shaper (TAS) ensures ultra-low jitter and bounded delays in Time-Sensitive Networks (TSN), assigning streams to queues and opening/closing gates through a Gate Control List (GCL). We propose a novel TAS implementation with a closed-loop controller replacing the GCL, enhancing robustness and network utilization while meeting critical requirements.